Analisis Efektivitas Digitalisasi Pajak Terhadap Kesadaran Wajib Pajak UMKM Kabupaten Tegal Dan Kepercayaan Kepada Pemerintah - Agnes Dwita Susilawati; Eva Anggra Yunita; Mei Rani Amalia (Universitas Katolik Soegijapranata, Semarang, 2023)
Tax is state revenues that have important role on development also is one of the elements in the APBN. General administration at the Tegal City Pratama Tax Service Office, improving the quality of employees, hire employees every year, and developing the use of e-filling applications. which experienced development and growth with a total of 140,042 people in 2019 who are engaged in 17 types of business fields (dinkop umkm Central Java, 2019). This study aims to provide empirical evidences based on effects of the effectiveness tax digitization on taxpayer awareness and government trust aware of taxpayer awareness. In this study, data was collected by distributes questionnaire to obtain a sample of 74 samples and then processed using SPSS 22 software. The data analysis technique is the form of quantitative data also used simple linear regressions data analysis. This study also shows there was positive influence in the effectiveness of tax digitization on taxpayer awareness and the positive influence of government trust on the awareness of Tegal Regency MSE taxpayers